2022
DOI: 10.1021/acsenergylett.2c01544
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Durable Nb(Ta)-Doped Proton Conductors for Reversible Solid Oxide Cells

Abstract: Proton-conducting reversible solid oxide cells (P-ReSOCs) are receiving increasing attention because they have potential to efficiently operate at intermediate temperatures to reduce cost and prolong operational life. Here we report our findings in the rational design of a new series of donor- and acceptor-codoped proton conductors through careful manipulation of defect chemistry. Specifically, BaNb­(Ta)0.05Ce0.7Yb0.25O3‑δ exhibits high ionic conductivity (0.012 S cm–1) while maintaining exceptional stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…[15] Small 2023, 19, 2208064 1) The results of Ce, Zr, Nb, and Ta are obtained from our previous work. [8] However, the optimized BM/WCYb05 materials still show slightly lower conductivity than the state-of-the-art proton conductor BZCYYb1711. In addition, we previously reported that 30% Yb-doped samples show poor chemical compatibility with NiO during cell fabrication, which could be detrimental to cell performance.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…[15] Small 2023, 19, 2208064 1) The results of Ce, Zr, Nb, and Ta are obtained from our previous work. [8] However, the optimized BM/WCYb05 materials still show slightly lower conductivity than the state-of-the-art proton conductor BZCYYb1711. In addition, we previously reported that 30% Yb-doped samples show poor chemical compatibility with NiO during cell fabrication, which could be detrimental to cell performance.…”
Section: Resultsmentioning
confidence: 98%
“…The lattice parameter observed here is slightly smaller than the Hf or Nb-containing materials we previously reported since W 6+ is smaller in size. [8,11] Figure 2d-i and Figure S3 (Supporting Information) show the HRTEM images and the corresponding energy-dispersive X-ray spectroscopy (EDS) elemental-mapping analysis of BWCYb powders, where all elements are uniformly distributed, suggesting the successful incorporation of W.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations